Perception of Higher Secondary Students About Technology Supported Learning in English Classroom - C. , Saravana perumal; H. , Deepa (International Journal of Psychosocial Rehabilitation, 2020)
Technology-supported learning is helpful in attaining the learning objectives. The paper examines the perception of higher secondary students about technology-supported learning in the English classroom. The survey method is used for collecting data for this study. The random sampling technique was used. Data gathered from 350 higher secondary students. The results indicated there is no significant difference between the perception of higher secondary students with regard to gender and location of the school. The results show that it is very important to make all the students learn with technology-supported learning in the English classroom.